Psychological complications of Cushing's syndrome. Issue 3 (June 2021) - Santos, Alicia; Webb, Susan M.; Resmini, Eugenia
Abstract : Purpose of review: The aim of this article is to review and discuss recent evidence of psychological complications in Cushing's syndrome. Recent findings: Recent research has described the presence of depression, anxiety, posttraumatic stress disorder, mania, bipolar disorder and psychotic symptoms in patients with Cushing's syndrome. Furthermore, the perspective of patients' partners has also been emphasized. Summary: Recent literature highlights the importance of screening for psychological alterations in Cushing's syndrome, as these alterations can be present in many patients, having a high impact in daily life. Depression is a very common symptom, although in rare cases, patients can also present mania or psychosis. Some studies highlight the importance of screening for organic disease (including Cushing's syndrome) in patients with unexpected or first onset psychiatric symptoms. Finally, the perspective of the patients' partners makes it clear that the partners can also suffer due to the disease of the patient. Intervention programmes involving patient's partners could be helpful to improve both patient and partner wellbeing.